An Example Approach for Taking of Auditory Comfort as a Design Parameter in Open Planned Offices - Ozdem Gurturk, Semran; Yugruk Akdag, Nese (Yildiz Technical Univ, Fac Architecture, 2020)
Noise audit is extremely important in creating an auditory environment suitable for the actions of users in volumes. On the other hand, due to the physical properties and functions of the volumes in certain buildings such as an open-plan office, industrial facility, noise is even a more important problem. Although open-plan offices make positive contributions to the business both in terms of costs and construction period, they also bring some problems especially for users. Studies to date reveal that the most important problem in many open-plan offices is noise. Since there are no partition walls in such places, sounds caused by speech, telephones and other office supplies, footsteps, air conditioning, and lighting noises, office equipment (i.e. (fax machines, printers), external noises reduce the efficiency of work and sometimes can lead to important health problems. As this clearly demonstrates, handling acoustic measures as a design parameter in the design of open-plan offices is a necessity. In this study, as an example of an open-plan office, a call center where the noise problem is very high was examined. Observations, surveys and measurements were carried out, then the volume was modeled and transferred to the Soundplan 8.1 program. The current noise level in the volume was first revealed by using the program. The call center model with the most appropriate acoustic comfort was sought to be determined in the same program by evaluating the number of personnel in the volume, suitable working unit model designs, divider element heights and different surface absorbents. The results of the current study regarding the measures to be taken to improve the audio environment within the scope of architectural and acoustic design may serve as a guide to the designers.
Keywords: Open plan office; acoustic comfort; acoustic design parameters